2021
DOI: 10.1080/00207160.2021.1952997
|View full text |Cite
|
Sign up to set email alerts
|

On the reliable and efficient numerical integration of the Kuramoto model and related dynamical systems on graphs

Abstract: In this work, a novel approach for the reliable and efficient numerical integration of the Kuramoto model on graphs is studied. For this purpose, the notion of order parameters is revisited for the classical Kuramoto model describing all-to-all interactions of a set of oscillators. First numerical experiments confirm that the precomputation of certain sums significantly reduces the computational cost for the evaluation of the right-hand side and hence enables the simulation of high-dimensional systems. In orde… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…We use the fourth order Runge-Kutta method [68] implemented in C++ in the GNU Scientific Library [69]. Here, it is important to highlight that several works have shown that in the numerical solution of equation ( 2), the results do not depend significantly on the integration method implemented or on the time step ∆t used to obtain numerical solutions [23,70,71].…”
Section: Synchronization Timesmentioning
confidence: 99%
“…We use the fourth order Runge-Kutta method [68] implemented in C++ in the GNU Scientific Library [69]. Here, it is important to highlight that several works have shown that in the numerical solution of equation ( 2), the results do not depend significantly on the integration method implemented or on the time step ∆t used to obtain numerical solutions [23,70,71].…”
Section: Synchronization Timesmentioning
confidence: 99%
“…However, not all community detection algorithms pursue to optimize on that feature. Therefore, we have analyzed and compared different community detection algorithms with respect to that feature [8].…”
Section: A1 Community Detection (P1)mentioning
confidence: 99%
“…For a very specialized and particular case, we have demonstrated recently that employing simple variants of the steps (E1)-(E2) and (P1)-(P2) can work potentially work [8]. In this work, we develop the general CIA framework and show that it works in an extremely broad class of network dynamics applications, that it is robustness with regard to real data sets, that the general method does yield linear computational complexity with respect to the dimensions of the systems, and that the steps naturally extend to higher-order/polyadic dynamics.…”
Section: Introductionmentioning
confidence: 99%